Review of the Stages of Physical Education (PE) Learning Planning Based on the Merdeka Curriculum - Asna Shofia; Arie Rakhman; Herita Warni (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This research aims to evaluate the stages of planning learning for Physical Education, Sports, and Health (PE) in the implementation of the Independent Curriculum in Junior High Schools in the tabuk river district.  This study uses a mixed-methods approach with quantitative analysis of the quality of teaching modules and qualitative analysis through in-depth interviews with four Physical Education (PE) teachers. The results show that none of the teaching modules analyzed reached the categories of ‘Good’ or ‘Very Good’, where 50% fell into the ‘Sufficient’ category and the other 50% ‘Poor’, indicating that the alignment of the modules with the principles of the Independent Curriculum has not yet been optimal. Qualitatively, it was found that teachers have understood the stages of planning from the analysis of learning outcomes to the development of assessments, but the implementation of initial assessments and differentiated learning is still minimal. The main challenges include limited training, inadequate facilities, and varying student motivation. Nevertheless, teachers demonstrate adaptive efforts through collaboration, the use of makeshift tools, and the utilization of digital media. This finding emphasizes the need for capacity building for teachers and resource support to ensure the successful implementation of the Merdeka Curriculum uniformly.